Effects of the MyBFF@school obesity intervention program with nutrition education intervention on nutrition knowledge and attitude of secondary schoolchildren: a cluster randomized controlled trial - Rusidah Selamat; Junidah Raib; Nur Azlina Abdul Aziz; Norlida Zulkafly; Ainan Nasrina Ismail; W Nurul Ashikin W Mohamad; Ainol Aizuddin Zulkiply; Muhammad Yazid Jalaludin; Fuziah Md. Zain; Zahari Ishak; Abqariyah Yahya; Abdul Halim Mokhtar (BMC Public Health)
Abstract Background The increasing global and national prevalence of childhood obesity particularly among schoolchildren has warranted a more viable school-based obesity intervention. Apart from physical activity, nutrition is important in any obesity intervention package. This study examined the effects of the MyBFF@school program with nutrition education intervention (NEI) on nutrition knowledge and attitude of overweight and obese secondary schoolchildren. Methods This is a cluster randomized controlled trial which involved schoolchildren aged 13, 14 and 16 years old from 15 out of 415 government secondary schools in central Peninsular Malaysia which were randomly assigned into six intervention (N = 579 schoolchildren) and nine control (N = 462 schoolchildren). The intervention group was given NEI consisting of a nutrition education module carried out by trained personnel for 24 weeks on top of the existing curriculum while the control group only followed the existing school curriculum by the Ministry of Education. The primary outcomes were the nutrition knowledge and attitude score. The mixed effect model taking into consideration the cluster effect was used to assess the changes of nutrition knowledge and attitude scores from baseline until 6 months. Results Overall, there was no significant increase in the adjusted mean difference (AMD) of nutrition knowledge score (AMD = 0.33%, Confident Interval (95 CI): -4.35% to 5.01) between the intervention and control group after 6 months of intervention after controlling for nutrition knowledge score at baseline, gender, location and ethnicity. Similarly, after controlling for the nutrition attitude score at baseline, ethnicity, location and gender as well as taking into account the cluster effects, there was no significant increase on the AMD of nutrition attitude score in the overall (AMD = 0.194, (95 CI): -1.17 to 1.56) and also among girls, location (urban vs rural) and Malays. There was also no significant reduction of AMD in the nutrition attitude score among boys and non-Malays. Conclusion MyBFF@school with NEI resulted with no significant improvement for nutrition knowledge and attitude among older schoolchildren. Therefore, to effectively impart the nutrition knowledge and change their nutrition attitude requires an in-depth study and multi-pronged and customized approach. Trial registration Clinical trial number: NCT04155255, November 7, 2019 (Retrospective registered). National Medical Research Register: NMRR-13–439-16563. Registered July 23, 2013. The intervention program was approved by the Medical Research and Ethics Committee (MREC), Ministry of Health Malaysia and Educational Planning and Research Division (EPRD), Ministry of Education Malaysia. It was funded by the Ministry of Health Malaysia.